Kebinet dalam sastra Gayo - Melalatoa, M. J. (Departemen Pendidikan dan Kebudayaan, Proyek Penerbitan Buku Sastra Indonesia dan Daerah, 1981)
Examples of a genre of oral literature of the Gayo people of Daerah Istimewa Aceh; includes an introduction to the form.